PENGOLAHAN LIMBAH CAIR UREA MENGGUNAKAN PROSES GABUNGAN ACTIVATED MICROALGAE DAN NITRIFIKASI-DENITRIFIKASI AUTOTROFIK: UJI DENGAN RANCANGAN TAGUCHI - Indro Sumantri; Sumarno Sumarno; Norma Afiati (Reaktor, 2012)
TREATMENT OF UREA WASTEWATER WITH COMBINED PROCESS OF ACTIVATED MICROALGAE AND NITRIFICATION-DENITRIFICATION AUTOTROPHIC: EVALUATION WITH TAGUCHI DESIGN. The conventional process for treatment wastewater from urea plant usually use of micro algae process or heterotrophic bacterial nitrification denitrification. Micro algae process use different type of micro algae. The advantage is cheap because used only little bit of P nutrient but cannot used for ammonium removal. Heterotrophic bacterial nitrification denitrification process needed high organic carbon input so that treatment cost so expensive. The objective of the research work was to investigate the potential of combination of special type micro algae process with an autotrophic nitrification-denitrification process. Micro algae species used in micro algae process have ability either for ammonium removal or withstand in high ammonium concentration. Autotrophic nitrification denitrification process used nitrifying bacterial/sludge as the biocatalyst. The origin of the nitrifying sludge was an activated sludge obtained from a particle board industry wastewater treatment plant where nitrification occurred in the aeration basin. Enrichment and breeding of the nitrifying sludge were conducted in high ammonium concentration and autotrophic condition. Based on experiment, enrichment and breeding micro algae which have ability either for ammonium removal or withstand in high ammonium concentration quite easy. By screening experiment with seven variable: MLSS, detention time, NH3-N concentration, aeration, CaCO3 concentration, micronutrient, N:P ratio, obtained the best level of variables are NH3-N concentration, aeration, CaCO3 concentration at high level. Evaluation limiting substrate inhibition of ammonium to nitrifying bacterial growth also unproved experimentally.Proses konvensional untuk mengolah limbah cair industri urea biasanya menggunakan proses alga mikro atau bakteri heterotropik nitrifikasi-denitrifikasi. Proses alga mikro dapat menggunakan berbagai jenis alga mikro. Keuntungannya adalah murah karena hanya memerlukan nutrien P sedikit tetapi tidak dapat digunakan untuk menyusutkan amoniak. Proses nitrifikasi-denitrifikasi bakteri heterotropik memerlukan asupan karbon yang tinggi sehingga pengolahan  menjadi mahal. Tujuan saat ini untuk penelitian adalah untuk mempelajari kombinasi yang potensial untuk proses alga mikro jenis tertentu dengan proses nitrifikasi-denitrifikasi ototrofik. Jenis alga mikro yang digunakan dalam proses alga mikro mempunyai kemampuan baik untuk penyusutan amoniak atau tahan dalam konsentrasi amoniak tinggi. Proses nitrifikasi-denitrifikasi ototrofik menggunakan bakteri nitrifikasi/lumpur sebagai biokatalis. Lumpur nitrifikasi awal adalah lumpur aktif kolam aerasi unit pengolahan limbah cair industri partikel board Pengayaan dan pembibitan lumpur nitrifikasi dilakukan dalam konsentrasi amoniak yang tinggi dan kondisi ototrofik. Berdasarkan penelitian, pengayaan dan pembibitan alga mikro yang mempunyai kemampuan untuk penyusutan amoniak dan tahan konsentrasi amoniak yang tinggi mudah. Evaluasi substrat pembatas penghambat amonium terhadap pertumbuhan alga tidak terbukti. Tujuh variabel yang dipilih lewat penapisan adalah : MLSS, waktu tinggal, konsentrasi NH3-N, laju aerasi, kadar CaCO3, nutrien mikro, rasio N:P. Variabel yang berpengaruhadalah konsentrasi NH3-N, laju aerasi, kadar CaCO3.Keywords: autotrophic nitrification-denitrification process; enrichment and breeding of the nitrifying sludge; micro algae proces